Empowerment, uso dos serviços e fatores associados em adultos brasileiros - Márcia de Fátima Soares (2014)
The present study aimed to characterize the adults residents in the surrounding municipalities of Belo Horizonte (urban area), Minas Gerais, Brazil, (1) testing the association of individual and collective empowerment and associated factors and (2) the association between features of using dental services among adults and associated factors. Methods: Cross-sectional study examined a complex probability sample of adults 35-44 years of both sexes, calculation was to estimate proportions, test power of 80%, a significance level of 5% and deff equal to 2.0 with correction for complex sample in all analyzes. Data were collected through interviews and examination of the oral cavity in households, after a pilot study (n = 98), whose participants were not included in the main study. For the analysis of individual and collective empowerment, the dependent variables were based on issues of IQ-MSC and the independent variables considered were sociodemographic status, lifestyle (adapted from the questionnaire Fantastic Lifestyle), quality of life (WHOQOL-Bref) and health oral (DMTF). In the analysis, the statistical software Stata (StataCorp LP version 12.0) was used. Logistic regression (collective empowerment) and multinomial (individual empowerment) recitals the variables associated with the empowerment of p <0.25 was performed. To evaluate the use of the services the dependent variable was obtained by combining three categories: regular use of dental services (yes or no), use in the last year (yes or no) and reason for use (pain or prevention / treatment). Were considered as independent variables demographic data, perceived health, oral health status, health behaviors and social capital (issues IQ-MSC). The ordinal logistic regression model of partial proportional odds was performed. Results: The study included 1150 adults, mostly female (66.63%), aged between 35 and 39 years (52.30%), brown skin (54.05%) lived with a partner (71.49 %). Most 5-11 years of education (50.58%), sedentary (61.95%), non-smoker (79.72%) and not consuming alcoholic beverages (61.13 %), average per capita income of US $ 225, living for 14.8 years at the same location. The mean DMFT was 16.91 and 68.58% reported perceiving their general health as bad or very bad. Most adults reported that probably people in the community would cooperate (62.91%) to solve the problem posed (water supply), but 59.82%, even feeling themselves able to make a decision to change the course of their own lives, declared non-participation in community activities. Associated to individual empowerment (p <0.25) variables were included in multivariate analysis, remaining significant: more years of schooling (5-11 and 12), perform a lot of physical activity, no smoking, feel able to decide upon their own lives, the psychological domain (WHOQOL) and lower DMFT.Variables associated with collective empowerment inserted in the multiple model (p <0.25) remained significant: Catholic religion, physical activity, consume or not consume little alcohol and all domains of quality of life (WHOQOL). Regarding the use of services, 34.4% reported making regular use of dental health services; 55.40% used last year and 68.80% used for treatment / prevention. A total of 273 adults (19.90%) had all the favorable characteristics for use of dental services. The optimal use of dental services was higher in those who reported to rely on social support (social capital), in those with higher income and higher education and those who do not have the smoking habit. The optimal use of dental services was lower among younger people, those with perceived general health good or very good. The increase in the number of decayed teeth was associated with a reduction in the chance of favorable use of dental services. From the variables related to social capital, remained significant the one that referred to have networks of friends and or family. Conclusions: Do more physical activity and aspects of quality of life were significantly associated with both the individual as to empowerment collective. Considering the interlock between them, physical activity for the empowerment of people and this will also lead to better quality of life, which probably will empower empowerment. Regarding the use of services, the favorable use was higher among those who reported relying on social support (social capital), had higher income, higher education and those who do not have the smoking habit.